Towards possible foundations for systematic orthodox sacramentology - Gzgzyan, D.M. (The Quarterly Journal of St. Philaret's Institute, 2021)
The article presents an attempt to define the reasons for absence of unified orthodox sacramental doctrine and therefor suggests possible foundations for building up one. The author’s understanding of sacramentum is based on vision of the nature of Church. The predominant until nowadays the so called clerical ecclesiological model limits the concept of completed sacramentum by a few formal conditions: presence of canonically justified priest, exclamation of a special sacramental formula, sacramental substance and a fixed moment of commitment. As a result this approach ignores the mystery of Church and The Holy Spirit acting freedom declared by the New Testament, and the basic significance of which was especially stressed by recognized Church authorities in different periods of Church history. Another foundation for an integral orthodox sacramental theory may be found in the experience of adult catechism practice which could be interpreted as the main Christian sacramental effort stemming from the high calling of the Church. Then the integral Church sacramentum appears to be an existential experience being therefore the core of Church existence including every separate act of entering the Church and also the general calling of the Church as it was explained by a number of notorious theologians. In this case The Church sacraments as well as the entire being of the Church turn into a dynamic process with unpredictable and varying results where their positivity is dependent on the quality of the spiritual efforts performed by a certain christial society. The efficacy of the sacraments should be therefore preferably described in terms of effort, trial and degree of commitment.